Sub-bacia hidrográfica do rio Poxim : transformação da paisagem (1970-2010) - Farias, Marta Cristina Vieira (2011)
The sub-basin of Poxim river (BHRP), with an area of 397 km2, is located in the eastern portion of Sergipe State (10 ° 55'-10 ° 45' S, 37 ° 05'-37 ° 22' W) and falls partially in the counties of Aracaju, São Cristóvão, Nossa Senhora do Socorro, Laranjeiras, Itaporanga d'Ajuda e Areia Branca. The population of the municipalities set out in its coastal portion, comprising the metropolitan area of Aracaju, close to 800,000 inhabitants, almost entirely set in the urban area. In order to analyze the environmental dynamics in the process of occupation of BHRP and the importance of natural resources available for development in the period between 1970 and 2010, we used the methodology of the integrated study of the landscape, according to the proposed Bovet Pla; Ribas Vilas (1992). We assessed the availability, use and vulnerability of natural resources, through the description of geo-environmental aspects - geology, geomorphology and climate; occurrence and soil characteristics, components of biodiversity - fauna and flora; availability, quality and demand for water resources, the socioeconomic factors - a history of regional occupation, development indicators, elements and factors of population growth, population dynamics, production activities and aspects of sanitation. Results showed that BHRP characterized by having their portion in an eminently coastal urbanized - fueled initially by government policies of industrialization and then by the construction of housing subdivisions and release - which is fully consolidated in Aracaju 1990. However, Nossa Senhora do Socorro and São Critóvão, adjacent to that, are subjected to the same phenomenon. They were recognized as natural resources available in BHRP components of biodiversity - fauna and terrestrial and aquatic flora, water resources, mineral resources and inventory of soils that, generally, have been used, often to the detriment of your stock. Land use, whether in urban or rural area, has promoted its depletion, such as removal of vegetation for human settlement and development of pastures and sugar cane plantations and illegal occupation of their margins. The BHRP stands out as an important source of supply of the RMA, particularly in Aracaju, which contributes approximately 30% and in the locality Grande Rosa Elze, supplying nearly 50.000 inhabitants. Also in São Cristóvão, the river Pitanga is used as the source, which contributes 10% of the supply of treated water and, likewise, suffers from human interference. To supply Aracaju in its entirety, the provision should be added to that enjoyed by the São Francisco river. The mineral resources such as sand and clay, have been widely used in the consolidation of the urban perimeter. The floodplain and the estuary of the rivers Pitanga and Poxim are used as depositories of effluents and untreated sewage, coming from industries and residences located on its banks, specifically in Nossa Senhora do Socorro. This leads to impairment of its quality for human supply. In Aracaju, better covered by sewage system, the river Poxim in its estuarine portion receives several discharges of sewage, so clandestine, residential and industrial, which may compromise the durability and quality of wildlife, especially intended for human consumption.